Survival analysis: A survey - Chung, Ching-Fan (Journal of quantitative criminology, 1991)
This paper is a survey of statistical methods used to analyze the length of time until a specified event occurs. These models have often been used to analyze the survival times (i.e., time until death) of medical patients, and so the term survival analysis is natural. In criminology, the main application of these models has been to analyze the time until recidivism, but many other applications are possible. The paper summarizes the statistical literature on survival analysis, and describes its applications in criminology. The methods are illustrated by an application to the prediction of time until recidivism for a sample of North Carolina prison releasees.